Spinal dysraphism controversies: AIIMS experiences and contribution - A.K. Mahapatra (Indian Journal of Neurosurgery)
A large series of split cord malformation (SCM). Over the last 22 years, we have operated more than 1500 patients of SD, of which over 450 are (SCM), and 300 are with various lipomatus malformations. About 55% type II and 45% type I SCM. A separate sub-classification of type I SCM (a,b,c and d), is presented which alter the surgical approach and influence the results. Overall improvement following surgery in patients with SCM was observed in 94%. Fifty percent patients improved and 44% remained stable. However, deterioration was noticed in 6%, mostly with composite type of SCM. A paradigm for management of SCM is provided taking into consideration also the author’s large experience.